Antibacterial hydrogel loaded with gold-iron phosphorus trisulfide nanosheets as well as preparation method and application of antibacterial hydrogel

By loading gold-iron trisulfide phosphorus nanosheets into antibacterial hydrogels, utilizing the GOx-POD cascade activity and photothermal therapy of Au-FePS3 nanosheets, combined with the antibacterial effect of quaternary ammonium salt chitosan, the problem on diabetic wounds is solved. It solves the difficult problems of antibacterial and hypoglycemic, and achieves simple and fast preparation method and efficient therapeutic effect.

CN119345358AActive Publication Date: 2025-01-24XIEHE HOSPITAL ATTACHED TO TONGJI MEDICAL COLLEGE HUAZHONG SCI & TECH UNIV

Patent Information

Application Number
CN202411484674.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-24
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

Existing nanoenzyme materials cannot achieve antibacterial and hypoglycemic effects on diabetic wounds, and the preparation method is complex and difficult to produce in large quantities.

Method used

Antibacterial hydrogels with load gold-three-sulfurized iron phosphorus nanopotic tablets produce ROS through the GOX-POD-level activity of AU-FEPS3 nanometer tablets, combined with the antibacterial effects of photocopia and daily ammonium salt-shell polycan, to achieve antibacterial and Hypoglybal effect.

Benefits of technology

The hydrogel simultaneously exerts antibacterial and hypoglycemic effects on diabetic wounds, and the preparation method is simple and fast, making it suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119345358A_ABST
    Figure CN119345358A_ABST
Patent Text Reader

Abstract

The invention provides antibacterial hydrogel loaded with gold-iron phosphorus trisulfide nanosheets as well as a preparation method and application of the antibacterial hydrogel, and belongs to the technical field of hydrogel materials. The preparation method comprises the following steps: loading a prepared Au-FePS3 nanosheet into quaternary ammonium salt chitosan (QC)-oxidized dextran (OD) hydrogel; the Au-FePS3 nanosheet has the activity of peroxidase (GOx), the activity of peroxidase (POD) and the photo-thermal characteristic, meanwhile, GOx and POD have cascade catalytic activity, active oxygen mainly including. OH is generated, and the antibacterial and hypoglycemic effects can be achieved on diabetic wounds at the same time; the QC-OD hydrogel has the effects of resisting bacteria, stopping bleeding, preserving moisture and slowly releasing a load, can promote wound healing, and has degradability and injectability; in addition, the Au-FePS3 nanosheet is loaded in the QC-OD hydrogel, so that agglomeration of the nano enzyme in the use process can be avoided, and the enzyme activity is enhanced. The preparation process of the Au-FePS3 nanosheet and the QC-OD hydrogel is simple and rapid, the production efficiency is high, the Au-FePS3 nanosheet and the QC-OD hydrogel are expected to be used for clinical treatment, and the life quality of a patient is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogel materials, and in particular to an antibacterial hydrogel loaded with gold-iron trisulfide phosphorus nanosheets, and a preparation method and application thereof. Background Art

[0002] The treatment of diabetic wounds has long been a severe challenge in clinical practice. Current clinical treatments for diabetic wounds include surgical debridement, dressings, antibiotics, negative pressure wound therapy, and hyperbaric oxygen therapy. However, the success rate of these traditional interventions is not ideal, with less than 50% of wounds being completely healed, and the treatment time is often long and the economic cost is high.

[0003] Enzymes, as powerful biocatalysts, are mainly composed of proteins, and a few are catalytic RNA molecules. While typical chemical catalysts or industrial catalysts are usually used under harsh conditions such as high temperature, high pressure, organic solvents, and extreme pH environments, enzymes are mainly used to catalyze the transformation of biomolecules, and these reactions are usually carried out under relatively mild conditions. Due to their high catalytic activity and high substrate specificity, natural enzymes have been widely used in industrial, medical, and biological fields. However, natural enzymes often have some inherent disadvantages, such as high preparation and purification costs, low operational stability, sensitivity to action conditions, and difficulty in recycling and reuse. In order to overcome these shortcomings, researchers have long been committed to the exploration of artificial enzymes. Nanozymes are nanomaterials with a similar reaction mechanism to natural enzymes, which have the advantages of low cost, high stability, and good durability. Based on the above excellent properties, nanozymes have been widely used in biosensing, environmental treatment, disease diagnosis and treatment, antibacterial agents, and cell protection of intracellular biomolecules. For example, Chinese patent CN111939270A discloses a dual nanozyme antibacterial agent with sustained antibacterial effect and a preparation method thereof, wherein the antibacterial agent has GOx-POD cascade activity and antibacterial ability; Chinese patent CN117772250A discloses a single-atom nanozyme based on an erythrocyte template, a preparation method and an application thereof, wherein the single-atom nanozyme has significant antibacterial properties; Chinese patent CN117462604A, a ebony charcoal nanozyme for promoting wound healing and its application. However, the nanozymes prepared by the above-mentioned prior art all lack hypoglycemic efficacy, have limited therapeutic ability for diabetic wounds, and their preparation methods are complicated and difficult to mass produce. Persistent bacterial infection and local high glucose levels are urgent problems to be solved in the treatment of diabetic wounds. At the same time, low-cost, simple preparation and application treatment methods are more likely to be applied. However, current nanozyme materials cannot meet the above requirements at the same time. Therefore, providing a method for preparing a nanozyme with a simple preparation process that simultaneously exerts antibacterial and hypoglycemic effects on diabetic wounds is a technical problem that the prior art urgently needs to solve. Summary of the invention

[0004] The purpose of the present invention is to provide an antibacterial hydrogel loaded with gold-iron trisulfide phosphorus nanosheets, and a preparation method and application thereof. The antibacterial hydrogel loaded with gold-iron trisulfide phosphorus nanosheets provided by the present invention has GOx activity, POD activity and photothermal properties, can simultaneously exert antibacterial and hypoglycemic effects on diabetic wounds, and the preparation method is simpler and faster.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing an antibacterial hydrogel loaded with gold-iron trisulfide phosphorus nanosheets, comprising the following steps:

[0007] (1) dispersing FePS3 crystals in N-methylpyrrolidone, and sequentially performing a first ultrasonic treatment and a first post-treatment to obtain FePS3 nanosheets;

[0008] The FePS3 nanosheets are formulated into a water dispersion of FePS3 nanosheets;

[0009] (2) mixing the aqueous dispersion of FePS3 nanosheets obtained in step (1) with polyvinyl pyrrolidone, adding HAuCl4·3H2O and NaBH4, and sequentially performing a second ultrasonic treatment and a second post-treatment to obtain Au-FePS3 nanosheets;

[0010] (3) adding sodium periodate solution to the dextran solution, performing redox reaction at room temperature in the dark, and then performing dialysis, low temperature standing and freeze drying in sequence to obtain oxidized dextran;

[0011] (4) preparing an aqueous solution of Au-FePS3 nanosheets obtained in step (2);

[0012] preparing an aqueous solution of oxidized dextran obtained in step (3);

[0013] The aqueous solution of the Au-FePS3 nanosheets, the aqueous solution of the oxidized dextran, the aqueous solution of quaternary ammonium chitosan and water are mixed, stirred and allowed to stand in sequence to obtain an antibacterial hydrogel loaded with gold-iron trisulfide phosphorus nanosheets.

[0014] Preferably, the concentration of the aqueous dispersion of FePS3 nanosheets in step (1) is 0.1 to 0.5 mg / mL.

[0015] Preferably, in step (2), the ratio of the volume of the aqueous dispersion of FePS3 nanosheets to the mass of polyvinyl pyrrolidone is 10 mL: (0.3-1) g.

[0016] Preferably, the ratio of the mass of FePS3 nanosheets in the aqueous dispersion of FePS3 nanosheets to the amount of HAuCl4·3H2O and NaBH4 in step (2) is 1 mg: (2×10 -3 ~8×10 -3 )mmol:(2×10 -3 ~8×10 -3 )mmol.

[0017] Preferably, in step (2), the molar ratio of the glucan monomer in the glucan solution to the sodium periodate in the sodium periodate solution is 1:(1-2).

[0018] Preferably, the concentration of Au-FePS3 nanosheets in the aqueous solution of Au-FePS3 nanosheets in step (4) is 0.5-2 mg / mL; the concentration of quaternary ammonium chitosan in the aqueous solution of quaternary ammonium chitosan is 5-10 wt%.

[0019] Preferably, the standing temperature in step (4) is 25 to 37° C., and the standing time is 2 to 10 minutes.

[0020] Preferably, the concentration of the quaternary ammonium salt chitosan-oxidized dextran hydrogel in the antibacterial hydrogel loaded with gold-phosphorus iron trisulfide nanosheets in step (4) is 3-7 wt %.

[0021] The present invention also provides an antibacterial hydrogel loaded with gold-iron trisulfide phosphorus nanosheets prepared by the preparation method described in the above technical scheme.

[0022] The present invention also provides the use of the antibacterial hydrogel loaded with gold-iron trisulfide phosphorus nanosheets described in the above technical solution in the preparation of diabetic wound treatment drugs.

[0023] The invention provides a method for preparing an antibacterial hydrogel loaded with gold-iron trisulfide phosphorus nanosheets. First, Au-FePS3 nanosheets are prepared and loaded in a quaternary ammonium salt chitosan (QC)-oxidized dextran (OD) hydrogel (referred to as QC-OD hydrogel); the Au-FePS3 nanosheets have both the peroxidase (GOx) activity of Au nanoparticles and the peroxidase (POD) activity and photothermal characteristics of FePS3, and GOx and POD have cascade catalytic activity, which can further generate active oxygen mainly composed of ·OH, and can simultaneously exert antibacterial and hypoglycemic effects on diabetic wounds; the QC-OD hydrogel has the effects of antibacterial, hemostatic, moisturizing and sustained release of the load, can further promote wound healing, and has degradability and injectability; in addition, the Au-FePS3 nanosheets are loaded in the QC-OD hydrogel, which can avoid the aggregation of nanozymes during use and enhance the enzyme activity. The novel nanosheet material prepared by the present invention provides a new direction for the treatment of diabetic wounds. The preparation process of Au-FePS3 nanosheets and QC-OD hydrogel is simple and rapid with high production efficiency, and is expected to be used in clinical treatment to improve the quality of life of patients. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 TEM image of FePS3 nanosheets prepared in Example 1 of the present invention;

[0025] Figure 2 TEM images and lattice images of Au-FePS3 nanosheets prepared in Example 1 of the present invention, wherein, from left to right, they are a TEM image with a scale of 100 nm, a TEM image with a scale of 10 nm, a TEM image with a scale of 5 nm, and a lattice image, wherein the upper image in the lattice image is FePS3, and the lower image is Au;

[0026] Figure 3 The elemental spectrum analysis diagram of the Au-FePS3 nanosheet prepared in Example 1 of the present invention, wherein the first row, from left to right, respectively includes a high-angle annular dark field scanning transmission image, an Au element diagram, and an Fe element diagram; the second row, from left to right, respectively includes a Merge (i.e., each element is merged) diagram, a P element diagram, and an S element diagram;

[0027] Figure 4 XRD pattern of Au-FePS3 nanosheets prepared in Example 1 of the present invention;

[0028] Figure 5 The graphs are the pH changes over time of the Au-FePS3 nanosheet dispersion, glucose solution and the mixed solution containing Au-FePS3 nanosheets and glucose of the present invention;

[0029] Figure 6The UV-visible absorption spectra of the glucose solution and the mixed solution containing Au-FePS3 nanosheets and glucose of the present invention are shown;

[0030] Figure 7 The Michaelis-Menten kinetic equation diagram of glucose of different concentrations after being treated with Au-FePS3 nanosheets of the present invention;

[0031] Figure 8 The absorbance statistics at 650 nm of PBS, H2O2 solution, Au-FePS3 nanosheet dispersion and mixed solution containing Au-FePS3 nanosheet and H2O2 of the present invention;

[0032] Fig. 9 This is the EPR spectrum of the Au-FePS3 nanosheets and hydrogen peroxide in PBS solution of the present invention;

[0033] Fig.10 The photothermal curves of Au-FePS3 nanosheet aqueous solutions with different concentrations in the present invention;

[0034] Fig.11 TEM images of the QC-OD hydrogels with concentrations of 3wt%, 5wt%, and 7wt% of the present invention and the QC-OD@Au-FePS3 hydrogel prepared in Example 1, wherein from left to right are the TEM image of the 3wt% QC-OD hydrogel, the TEM image of the 5wt% QC-OD hydrogel, the TEM image of the 7wt% QC-OD hydrogel, and the TEM image of the QC-OD@Au-FePS3 hydrogel prepared in Example 1 (abbreviated as 5%+Au-FePS3);

[0035] Fig.12 The elemental map scanning result diagram of the QC-OD@Au-FePS3 hydrogel prepared in Example 1 of the present invention, wherein the first row, from left to right, are the Merge (i.e., the elements are merged) diagram, the C element diagram, the O element diagram, and the N element diagram; the second row, from left to right, are the Au element diagram, the Fe element diagram, the P element diagram, and the S element diagram;

[0036] Fig.13 The rheological results of QC-OD hydrogels (without Au-FePS3 nanosheets) with concentrations of 3wt%, 5wt%, and 7wt% in the present invention are shown in the figure on the left, which changes with time, and the figure on the right changes with frequency. The storage modulus is referred to as G', and the loss modulus is referred to as G".

[0037] Fig.14 FTIR graph of QC-OD hydrogel (without loading Au-FePS3 nanosheets) with a concentration of 5 wt% in the present invention;

[0038] Fig.15 The graphs of the swelling rate and degradation rate of the QC-OD hydrogels with concentrations of 3wt%, 5wt% and 7wt% respectively in the present invention over time, wherein the left graph is the swelling rate and the right graph is the degradation rate;

[0039] Fig.16 The self-healing and adhesion physical pictures of the QC-OD hydrogel with a concentration of 5 wt% in the present invention, wherein from left to right are the physical pictures of cutting, adhesion and healing within 5 minutes;

[0040] Fig.17 This is a physical picture of the injectability of the QC-OD hydrogel with a concentration of 5 wt% in the present invention;

[0041] Fig.18 The actual picture of mouse liver treated with the blank control group, hemostatic sponge, QC-OD hydrogel with a concentration of 5wt% and QC-OD@Au-FePS3 hydrogel prepared in Example 1 in the present invention, wherein from left to right are the blank control group, hemostatic sponge, QC-OD hydrogel with a concentration of 5wt% and QC-OD@Au-FePS3 hydrogel prepared in Example 1;

[0042] Fig.19 This is a physical picture of the changes of the infected wound surface of diabetic rats over time after different treatments in the present invention;

[0043] Fig. 20 The diagram is a diagram of the antibacterial effect in the infected wound of diabetic rats after different treatments in the present invention, wherein from left to right are PBS treatment, 5wt% QC-OD hydrogel treatment, QC-OD@Au-FePS3 hydrogel treatment prepared in Example 1, and NIR and QC-OD@Au-FePS3 hydrogel treatment prepared in Example 1;

[0044] Fig.21 This is a flow chart of preparing an antibacterial hydrogel loaded with gold-iron trisulfide phosphorus nanosheets according to Example 1 of the present invention. DETAILED DESCRIPTION

[0045] The present invention provides a method for preparing an antibacterial hydrogel loaded with gold-iron trisulfide phosphorus nanosheets, comprising the following steps:

[0046] (1) dispersing FePS3 crystals in N-methylpyrrolidone, and sequentially performing a first ultrasonic treatment and a first post-treatment to obtain FePS3 nanosheets;

[0047] The FePS3 nanosheets are formulated into a water dispersion of FePS3 nanosheets;

[0048] (2) mixing the aqueous dispersion of FePS3 nanosheets obtained in step (1) with polyvinyl pyrrolidone, adding HAuCl4·3H2O and NaBH4, and sequentially performing a second ultrasonic treatment and a second post-treatment to obtain Au-FePS3 nanosheets;

[0049] (3) adding sodium periodate solution to the dextran solution, performing gelation reaction at room temperature in the dark, and then performing dialysis, low temperature standing and freeze drying in sequence to obtain oxidized dextran;

[0050] (4) preparing an aqueous solution of Au-FePS3 nanosheets obtained in step (2);

[0051] preparing an aqueous solution of oxidized dextran obtained in step (3);

[0052] The aqueous solution of the Au-FePS3 nanosheets, the aqueous solution of the oxidized dextran, the aqueous solution of quaternary ammonium chitosan and water are mixed, stirred and allowed to stand in sequence to obtain an antibacterial hydrogel loaded with gold-iron trisulfide phosphorus nanosheets.

[0053] In the present invention, unless otherwise specified, the raw materials used are conventional commercial products in the art.

[0054] The present invention disperses FePS3 crystals in N-methylpyrrolidone, and sequentially performs a first ultrasonic treatment and a first post-treatment to obtain FePS3 nanosheets.

[0055] In the present invention, the particle size of the FePS3 crystal is preferably 50 to 200 nm.

[0056] In the present invention, the concentration of the FePS3 crystal dispersion obtained by dispersing FePS3 crystals in N-methylpyrrolidone is preferably 1 to 7 mg / mL, and more preferably 1.5 to 4 mg / mL.

[0057] In the present invention, the power of the first ultrasonic treatment is 500-800 W, more preferably 600 W; the time of the first ultrasonic treatment is 12-18 h, more preferably 13-17 h, and further preferably 15 h. The present invention controls the power and time of the first ultrasonic treatment within the above range to promote the exfoliation of FePS3 crystals.

[0058] Obtain high-quality FePS3 crystals

[0059] In the present invention, the first post-treatment comprises centrifugation, washing and drying in sequence.

[0060] In the present invention, the centrifugation and washing are preferably centrifuging the solution obtained by the first ultrasonic treatment at 4000 rpm for 10 minutes to remove large pieces, then centrifuging the supernatant at 14000 rpm for 30 minutes, washing the obtained precipitate with ethanol and centrifuging at 14000 rpm for 30 minutes, collecting the precipitate, and then washing with water and centrifuging at 14000 rpm for 30 minutes to collect the precipitate. In the present invention, the drying is preferably freeze drying or drying in an oven, more preferably freeze drying. In the present invention, the freeze drying is preferably freezing the precipitate obtained by the centrifugation at -20°C for 12 hours, and then drying it in a freeze dryer at a pressure of less than 3.0 Pa and a temperature of less than -80°C for 72 hours.

[0061] In the present invention, the transverse diameter of the FePS3 nanosheet is preferably 50 to 200 nm, more preferably 100 nm. The present invention controls the transverse diameter of the FePS3 nanosheet within the above range to improve the enzyme activity and photothermal properties of the unit mass of Au-FePS3 nanosheets prepared subsequently, thereby improving the therapeutic effect of the antibacterial hydrogel finally prepared on diabetic wounds.

[0062] After obtaining the FePS3 nanosheets, the present invention prepares the FePS3 nanosheets into a water dispersion of the FePS3 nanosheets.

[0063] In the present invention, the concentration of the aqueous dispersion of the FePS3 nanosheets is preferably 0.1 to 0.5 mg / mL. The present invention controls the concentration of the aqueous dispersion of the FePS3 nanosheets within the above range to regulate the uniform size of the subsequently prepared Au-FePS3 nanosheets, improve the enzyme activity and photothermal properties of the Au-FePS3 nanosheets, and thus improve the therapeutic effect of the finally prepared antibacterial hydrogel on diabetic wounds.

[0064] After obtaining the aqueous dispersion of FePS3 nanosheets, the present invention mixes the aqueous dispersion of FePS3 nanosheets with polyvinyl pyrrolidone, then adds HAuCl4·3H2O and NaBH4, and sequentially performs a second ultrasonic treatment and a second post-treatment to obtain Au-FePS3 nanosheets;

[0065] In the present invention, the volume ratio of the aqueous dispersion of the FePS3 nanosheets to the mass ratio of polyvinyl pyrrolidone is preferably 10 mL: (0.3-1) g, more preferably 10 mL: (0.4-0.7) g, and further preferably 10 mL: 0.6 g. In the present invention, the mixing method of the aqueous dispersion of the FePS3 nanosheets and polyvinyl pyrrolidone is preferably ultrasonic dispersion at a power of 400 W for 20-50 min.

[0066] In the present invention, the mass ratio of the FePS3 nanosheets in the aqueous dispersion of the FePS3 nanosheets to the amount of HAuCl4·3H2O and NaBH4 is preferably 1 mg: (2×10 -3 ~8×10 -3 )mmol:(2×10 -3 ~8×10 -3 )mmol, more preferably 1mg: (4×10 -3 ~7×10 -3 )mmol:(4×10 -3 ~7×10 -3 In the present invention, the molar ratio of HAuCl4·3H2O to NaBH4 is preferably 1:1.

[0067] In the present invention, the time of the second ultrasonic treatment is preferably 20 to 50 minutes; the power of the second ultrasonic treatment is preferably 400W. In the present invention, the second post-treatment preferably includes centrifugation, water washing and drying. In the present invention, the centrifugation and washing are preferably centrifuged at 14000rpm for 30 minutes, the obtained precipitate is washed with water and then centrifuged at 14000rpm for 30 minutes, and the precipitate is collected. In the present invention, the drying is preferably freeze drying or drying in an oven, more preferably freeze drying. In the present invention, the freeze drying is preferably to freeze the precipitate obtained by centrifugation at -20°C for 24 hours, and then dry it in a freeze dryer at an air pressure of <3.0pa and a temperature of <-80°C for 72 hours.

[0068] In the present invention, the transverse diameter of the Au-FePS3 nanosheet is preferably 150-300 nm, more preferably 200 nm. In the present invention, the diameter of the Au nanoparticles on the Au-FePS3 nanosheet is preferably 1-10 nm, more preferably 2-5 nm.

[0069] The invention adds sodium periodate solution into dextran solution, performs gelation reaction at room temperature and in the dark, and then performs dialysis, low temperature standing and freeze drying in sequence to obtain oxidized dextran.

[0070] In the present invention, the concentration of sodium periodate in the sodium periodate aqueous solution is preferably 80-120 g / L, more preferably 100 g / L. In the present invention, the molar ratio of the glucan monomer in the glucan solution to the sodium periodate in the sodium periodate solution is preferably 1:(1-2), more preferably 1:1.5. The present invention controls the molar ratio of the glucan monomer in the glucan solution to the sodium periodate in the sodium periodate solution within the above range to improve the toughness of the subsequently prepared hydrogel.

[0071] In the present invention, the gelation reaction time is preferably 4 to 8 hours, more preferably 6 hours. In the present invention, the dialysis is preferably performed using a dialysis bag with a molecular weight cutoff (MwCO) of 3500 for 2 to 4 days, and the dialysis fluid is replaced every day until the dialysis fluid remains clear and colorless after 1 day of dialysis. In the present invention, the low-temperature standing is preferably standing at -80°C for 1 day. In the present invention, the freeze-drying is preferably dried in a freeze dryer at an air pressure of ≤3.0pa and a temperature of ≤-80°C for 72 hours.

[0072] After obtaining the Au-FePS3 nanosheets, the present invention prepares the Au-FePS3 nanosheets into an aqueous solution of Au-FePS3 nanosheets.

[0073] In the present invention, the concentration of Au-FePS3 nanosheets in the aqueous solution of Au-FePS3 nanosheets is preferably 0.5 to 2 mg / mL, more preferably 0.8 to 1.5 mg / mL.

[0074] After obtaining the oxidized dextran, the present invention prepares the oxidized dextran into an aqueous solution of oxidized dextran.

[0075] In the present invention, the concentration of oxidized dextran in the aqueous solution of oxidized dextran is preferably 5 to 10 wt %, more preferably 7 wt %.

[0076] After obtaining an aqueous solution of Au-FePS3 nanosheets and an aqueous solution of oxidized dextran, the present invention mixes the aqueous solution of Au-FePS3 nanosheets, the aqueous solution of oxidized dextran, the aqueous solution of quaternary ammonium chitosan and water, and stirs and stands the mixture in sequence to obtain an antibacterial hydrogel loaded with gold-iron trisulfide phosphorus nanosheets.

[0077] In the present invention, the concentration of quaternary ammonium salt chitosan in the aqueous solution of quaternary ammonium salt chitosan is preferably 5-10wt%, more preferably 7wt%.

[0078] In the present invention, the stirring speed is preferably 100-150 rpm, more preferably 120 rpm; the stirring time is preferably 10s-1min, more preferably 0.5min. In the present invention, the standing temperature is preferably 25-37°C; the standing time is preferably 2-10min. The present invention controls the stirring and standing conditions within the above range, which is conducive to gelation, and obtains an antibacterial hydrogel loaded with gold-iron trisulfide phosphorus nanosheets with good comprehensive performance.

[0079] In the present invention, the concentration of the quaternary ammonium salt chitosan-oxidized dextran hydrogel in the antibacterial hydrogel loaded with gold-phosphorus iron trisulfide nanosheets is preferably 3-7wt%, more preferably 5wt%.

[0080] The preparation method of the Au-FePS3 nanosheets provided by the present invention is simple, does not require complicated instruments and equipment, has low cost, and is expected to be used for industrial production; the QC-OD hydrogel raw material is easy to obtain, the preparation method is simple, and a large amount can be prepared at a single time; the ultra-high specific surface area of ​​the FePS3 nanosheets prepared by the present invention is not only conducive to the loading of Au nanoparticles, but also can promote the surface / interface mediated POD catalytic reaction process. At the same time, the use of QC-OD hydrogel loading avoids the agglomeration of nanozymes and further ensures the enzymatic reaction activity; the Au-FePS3 nanosheets prepared by the present invention can consume local glucose and alleviate oxidative stress, vascular and neuropathy caused by a high-sugar environment.

[0081] The present invention also provides an antibacterial hydrogel loaded with gold-iron trisulfide phosphorus nanosheets prepared by the preparation method described in the above technical scheme.

[0082] The antibacterial hydrogel loaded with gold-iron trisulfide phosphorus nanosheets in the present invention can generate ROS through the GOx-POD cascade activity of Au-FePS3 nanosheets, and cooperate with the quaternary ammonium salt groups in photothermal therapy and QC-OD hydrogel to fight bacteria and solve the infection problem, wherein the quaternary ammonium salt groups give chitosan solubility, and the negatively charged characteristics can adsorb bacteria and increase the permeability of bacterial membranes. On this basis, the ROS generated by the POD activity can more easily enter the bacteria, exert antibacterial properties, and then produce a synergistic antibacterial effect; the local heat therapy mediated by the Au-FePS3 nanosheets can promote local blood circulation in the wound, thereby increasing oxygen supply, improving the hypoxic microenvironment, and promoting the proliferation and migration of fibroblasts and vascular endothelial cells, thereby promoting wound healing; and the QC-OD hydrogel has the effects of antibacterial, hemostasis, moisturizing, and sustained release of the load, as well as degradability and injectability.

[0083] The present invention also provides the use of the antibacterial hydrogel loaded with gold-iron trisulfide phosphorus nanosheets described in the above technical solution in the preparation of diabetic wound treatment drugs.

[0084] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0085] Example 1

[0086] A method for preparing an antibacterial hydrogel loaded with gold-iron trisulfide phosphorus nanosheets comprises the following steps:

[0087] (1) 100 mg of FePS3 crystals were dispersed in 50 mL of N-methylpyrrolidone (NMP, AR, >99.0%), and then subjected to the first ultrasonic treatment in an ice bath at 600 W for 15 h, with an ultrasonic working time of 5 seconds and an interval of 3 seconds. The solution obtained by the first ultrasonic treatment was centrifuged at 4000 rpm for 10 min to remove large pieces, and then the supernatant was centrifuged at 14000 rpm for 30 min to obtain the precipitate. The precipitate was washed with ethanol and centrifuged at 14000 rpm for 30 min. The precipitate was collected and washed with water and centrifuged at 14000 rpm for 30 min. After centrifugation for 30 min, the precipitate was collected and frozen at -20 °C for 12 h, and then dried in a freeze dryer at a pressure of <3.0 Pa and a temperature of <-80 °C for 72 h to obtain 35 mg of FePS3 nanosheets;

[0088] Disperse 4 mg of FePS3 nanosheets in 40 mL of water to obtain an aqueous dispersion of FePS3 nanosheets;

[0089] (2) Add 2.4 g of polyvinyl pyrrolidone to the aqueous dispersion of FePS3 nanosheets obtained in step (1), and ultrasonically disperse for 30 min. Then add 2 mL of HAuCl4·3H2O (10 mM) and 2 mL of NaBH4 (10 mM), and perform a second ultrasonic treatment at 400 W for 30 min. Centrifuge the solution obtained by the second ultrasonic treatment at 14000 rpm for 30 min. Wash the obtained precipitate with water, and then centrifuge it at 14000 rpm for 30 min. Collect the precipitate, freeze it at -20°C for 24 h, and then dry it in a freeze dryer at an air pressure of 2.0 Pa and a temperature of -80°C for 72 h to obtain 5 mg of Au-FePS3 nanosheets.

[0090] (3) Weigh 10 g of dextran and dissolve it in 100 mL of deionized water to obtain a dextran solution; prepare a sodium periodate aqueous solution with a concentration of 100 g / L of sodium periodate according to a molar ratio of dextran monomer to sodium periodate of 1:1.5; add the sodium periodate solution to the dextran solution, perform gelation reaction at room temperature in the dark for 6 h, and then add 2 mL of ethylene glycol to terminate the reaction; dialyze using a dialysis bag with a molecular weight cutoff (MwCO) of 3500, replace the dialysis solution every day, and the dialysis solution is clear and colorless on the third day. After the dialysis solution is placed in a -80°C refrigerator for 1 day, it is placed in a freeze dryer for freeze drying to obtain a white product, oxidized dextran;

[0091] (4) preparing the Au-FePS3 nanosheets obtained in step (2) into an aqueous solution of Au-FePS3 nanosheets with a concentration of 1 mg / mL;

[0092] The oxidized dextran obtained in step (3) is prepared into an oxidized dextran aqueous solution having an oxidized dextran concentration of 7 wt %;

[0093] 200uL of the aqueous solution of the Au-FePS3 nanosheets, 357uL of the aqueous solution of the oxidized dextran, 357uL of the aqueous solution of quaternary ammonium chitosan with a concentration of 7wt% and 86uL of deionized water were mixed, stirred at 120rpm for 0.5min, and then allowed to stand at 37°C for 5min to obtain 1mL of the antibacterial hydrogel loaded with gold-iron trisulfide phosphorus nanosheets (abbreviated as QC-OD@Au-FePS3 hydrogel);

[0094] The concentration of QC-OD hydrogel in the antibacterial hydrogel loaded with gold-phosphorus iron trisulfide nanosheets is 5wt%.

[0095] Fig.21 This is a flow chart of preparing an antibacterial hydrogel loaded with gold-iron trisulfide phosphorus nanosheets according to Example 1 of the present invention.

[0096] The TEM image of the FePS3 nanosheets prepared in Example 1 was obtained by using Talos F200S, Thermo Fisher Scientific (USA). Figure 1 As shown. Figure 1 It can be seen that the lateral diameter of the FePS3 nanosheets prepared in Example 1 is 100 nm.

[0097] The TEM image and lattice image of the Au-FePS3 nanosheet prepared in Example 1 were obtained by using Talos F200S, Thermo Fisher Scientific (USA). Figure 2 As shown. Figure 2 It can be seen that the lateral diameter of the Au-FePS3 nanosheet prepared in Example 1 is 200 nm, wherein the Au nanoparticles are evenly dispersed on the nanosheet with a diameter of 2 to 5 nm, and the lattice formation of Au and FePS3 can be seen, indicating that its microscopic physical structure is well preserved.

[0098] The elemental spectrum analysis of the Au-FePS3 nanosheets prepared in Example 1 was obtained by using Talos F200S, Thermo Fisher Scientific (USA). Figure 3 As shown. Figure 3 Strong signals of Au, Fe, P and S elements can be observed, which proves that the Au-FePS3 nanosheets prepared in Example 1 have good element distribution and are consistent with Figure 2 The observation results are consistent.

[0099] The XRD pattern of the Au-FePS3 nanosheets prepared in Example 1 was obtained by SmartLab, Rigaku (Japan). Figure 4 As shown by Figure 4It can be seen that by comparing with the pure phase XRD spectrum, the phase of the sample was preliminarily confirmed (PDF#02-1095, PDF#33-0672), indicating that the Au-FePS3 nanosheets prepared in Example 1 are composed of Au and Fe2P2S6.

[0100] Activity identification of Au-FePS3 nanosheets (i.e. GOx / POD enzyme) prepared in Example 1

[0101] The detection method is as follows: prepare a Au-FePS3 nanosheet (prepared in Example 1) dispersion with a concentration of 0.20 mg / mL, a 40 mM glucose solution, and a mixed solution with a concentration of 0.20 mg / mL Au-FePS3 nanosheet (prepared in Example 1) and a glucose concentration of 40 mM, respectively, and detect the pH value changes of the above different solutions over time, and use the pH value to indicate the formation of gluconic acid, to obtain the pH change of the Au-FePS3 nanosheet dispersion, the glucose solution, and the mixed solution containing the Au-FePS3 nanosheet and glucose over time as shown in the figure. Figure 5 As shown by Figure 5 It can be seen that the significant decrease in the pH of the mixed solution indicates the formation of gluconic acid, indicating that Au-FePS3 nanosheets can decompose glucose and generate gluconic acid.

[0102] UV-Vis absorption spectra of different reaction solutions

[0103] Detection method 2: The glucose concentration in a 40 mM glucose solution and a mixed solution of 0.20 mg / mL Au-FePS3 nanosheets (prepared in Example 1) and 40 mM glucose concentration was detected by a glucose detection kit, and the UV-visible absorption spectra of the glucose solution and the mixed solution containing Au-FePS3 nanosheets and glucose were obtained as shown in FIG. Figure 6 As shown by Figure 6 It can be seen that the significant decrease in the absorbance of the mixed solution indicates a decrease in the glucose concentration, indicating that the Au-FePS3 nanosheets prepared in Example 1 can decompose glucose.

[0104] In addition, the prior art Chinese patent CN118477099A discloses an AuNPs@MOF nanozyme, which lacks antibacterial effect and cannot solve the infection problem in diabetic wounds, and the technical solution does not quantify the GOx enzyme activity. However, the present invention quantifies the GOx enzyme activity.

[0105] Michaelis-Menten kinetic analysis of Au-FePS3 nanosheets prepared in Example 1 using glucose as substrate

[0106] Detection method: In the presence of 0.20 mg / mL Au-FePS3 nanosheets (prepared in Example 1) in glucose concentrations of 2.5, 5, 10, 20, 50 and 100 mM solutions, the glucose concentration after 1 min was measured, and the corresponding Michaelis-Menten kinetic equation was calculated using glucose as the substrate. The Michaelis-Menten kinetic equation of glucose at different concentrations after treatment with Au-FePS3 nanosheets was obtained as shown in the figure. Figure 7 As shown by Figure 7 As shown, the Au-FePS3 nanosheets prepared in Example 1 have good GOx catalytic activity.

[0107] Absorbance detection method of different reaction solutions at 650nm: prepare four groups of different reaction solutions and add them into four 1.5mL centrifuge tubes respectively, among which, in the PBS group, add 490uLPBS (pH=7.4), 10uLTMB (10mg / mL); in the H2O2 group, add 440uLPBS (pH=7.4), 10uLTMB (10mg / mL), 50uLH2O2 solution (0.1M); in the Au-FePS3 group, add 480uLPBS (pH=7.4), 10uLTMB (10mg / mL), 10uL Au-FePS3 nanosheet (prepared in Example 1) dispersion (10 mg / mL); in the Au-FePS3+H2O2 group, 430uL PBS (pH=7.4), 10uL TMB (10 mg / mL), 50uL H2O2 solution (0.1M), and 10uL Au-FePS3 nanosheet (prepared in Example 1) dispersion (10 mg / mL) were added. After the different reaction solutions in the centrifuge tubes reacted for 10s, they were centrifuged at 12000rpm for 5min respectively. The supernatant was added to a 96-well plate, and the absorbance at 650nm was detected to obtain the absorbance statistics of PBS, H2O2 solution, Au-FePS3 nanosheet dispersion (i.e., Au-FePS3 group) and the mixed solution containing Au-FePS3 nanosheets and H2O2 (i.e., Au-FePS3+H2O2 group) at 650nm as shown in the figure. Figure 8 As shown by Figure 8 It can be seen that the Au-FePS3 nanosheets prepared in Example 1 can mediate the color development reaction of TMB, proving that it has POD catalytic activity.

[0108] EPR spectra of Au-FePS3 nanosheets prepared in Example 1 and hydrogen peroxide in PBS solution

[0109] Detection method: DMPO was used as the capture agent, and the reaction was carried out in a dark environment for 1 minute. The equipment used was German Bruker EMXplus-6 / 1. The EPR spectra of Au-FePS3 nanosheets and hydrogen peroxide in PBS solution were obtained as shown below: Fig. 9 As shown. Fig. 9 It can be seen that the EPR spectrum proves that the ROS produced by the Au-FePS3 nanosheets prepared in Example 1 catalyzing H2O2 is mainly ·OH.

[0110] Identification of the photothermal capability of the Au-FePS3 nanosheets prepared in Example 1

[0111] Detection method: Different concentrations of Au-FePS3 nanosheets (0, 0.05, 0.10, 0.20 mg / mL) were placed in a 400 nm wavelength and a power of 0.8 W / cm 2 The laser was irradiated for 5 minutes, and the real-time temperature was recorded to obtain the photothermal curves of Au-FePS3 nanosheet aqueous solutions with different concentrations. Fig.10 As shown by Fig.10 It can be seen that the Au-FePS3 nanosheets prepared in Example 1 have excellent photothermal capacity, and the photothermal temperature can be adjusted by the material concentration.

[0112] In addition, the prior art Chinese patent CN117772250A discloses a single-atom nanozyme based on an erythrocyte template, its preparation method and application, but the photothermal temperature of the single-atom nanozyme based on an erythrocyte template can reach 70°C, which can cause damage to human tissues. The above-mentioned prior art CN117772250A does not explore the adjustability of the photothermal capacity of the nanozyme. The Au-FePS3 nanosheets prepared by the present invention have a suitable photothermal temperature and will not cause damage to the human body. At the same time, the present invention explores the photothermal characteristics of different Au-FePS3 nanosheet solution concentrations and different NIR powers.

[0113] Characterization of QC-OD@Au-FePS3 hydrogel prepared in Example 1

[0114] Detection method: According to the method of Example 1, QC-OD hydrogels (without loading Au-FePS3 nanosheets) with concentrations of 3wt%, 5wt%, and 7wt% were prepared respectively. Sigma 300 (Carl Zeiss AG, Germany) was used to detect the TEM images of QC-OD hydrogels with concentrations of 3wt%, 5wt%, and 7wt% and the QC-OD@Au-FePS3 hydrogel prepared in Example 1. Fig.11 As shown by Fig.11It can be seen that QC-OD hydrogels of different concentrations have a loose and porous structure and have the ability to load the nanozyme Au-FePS3, and in the QC-OD@Au-FePS3 hydrogel prepared in Example 1, Au-FePS3 is evenly distributed in the gaps of the QC-OD hydrogel.

[0115] The elemental spectrum scanning results of the QC-OD@Au-FePS3 hydrogel prepared in Example 1 were obtained by Sigma 300 (Carl Zeiss AG, Germany) as shown in Figure 12. Fig.12 It can be seen that in the QC-OD@Au-FePS3 hydrogel prepared in Example 1, the Au-FePS3 nanosheets are evenly distributed in the hydrogel network.

[0116] Rheological results of QC-OD hydrogels with different concentrations

[0117] Detection method: The QC-OD hydrogels (without Au-FePS3 nanosheets) prepared by the above method with concentrations of 3wt%, 5wt%, and 7wt% were tested using a Mars40 rheometer (Haake Technik GmbH, Germany) in parallel plate mode; in the time scan, the strain and frequency were fixed at 1% and 1Hz, respectively. In the frequency scan, the strain was fixed at 1%, and the rheological results of the QC-OD hydrogels (without Au-FePS3 nanosheets) with concentrations of 3wt%, 5wt%, and 7wt% were shown in the figure below. Fig.13 As shown, Fig.13 The middle right picture shows the rheological frequency sweep. Fig.13 The left picture in the middle is the rheological time scan. Fig.13 It can be seen that QC-OD hydrogel exhibits appropriate storage modulus (G') and loss modulus (G"), which is consistent with the hydrogel characteristics.

[0118] FTIR results of QC-OD hydrogel

[0119] Detection method: The FTIR image of QC-OD hydrogel (without Au-FePS3 nanosheets) with a concentration of 5 wt% was obtained by using Nicolet iS20 (Thermo Fisher Scientific, USA). Fig.14 As shown by Fig.14 It can be seen that FTIR further proves the formation of QC-OD hydrogel. QC-OD hydrogel has a peak at 1652 cm -1 The peak at 3430 cm indicates a carbon-nitrogen double bond, proving the formation of a Schiff bond. The remaining peaks correspond to the monomers, 3430 cm -1 The peak at 2921 cm corresponds to the stretching vibration of OH. -1 and 1480cm -1The peaks at 1379 cm-1 correspond to the asymmetric stretching vibration and bending vibration of -CH2 in quaternary ammonium chitosan. -1 The peak corresponds to the bending vibration of -CHO in oxidized dextran, 1069 cm -1 The peak corresponds to the stretching vibration of CO.

[0120] Swelling and degradation rates of QC-OD hydrogels with different concentrations

[0121] Detection method: Swelling: The QC-OD hydrogels (without Au-FePS3 nanosheets) prepared above with concentrations of 3wt%, 5wt%, and 7wt% were immersed in 1mL PBS, and weighed at specific time points (0, 1, 2, 4, 6, 8, 10, 12, 16, and 24h); before measuring the weight of the hydrogel sample, the surface moisture was removed, and the swelling rate was calculated as follows:

[0122]

[0123] Where W0 is the initial weight of the hydrogel sample, and Wn is the weight of the hydrogel sample after n hours.

[0124] Degradation: The QC-OD hydrogels (without Au-FePS3 nanosheets) prepared above with concentrations of 3wt%, 5wt%, and 7wt% were immersed in 1mL PBS, taken out at specific time points (0, 4, 8, 12, 16, 24, 48, and 72h), freeze-dried, and weighed. The degradation rate was calculated as follows:

[0125]

[0126] Where Wd0 is the initial dry weight of the hydrogel sample, and Wdn is the dry weight of the hydrogel sample after n hours.

[0127] The above test results show that the swelling rate and degradation rate of QC-OD hydrogels with concentrations of 3wt%, 5wt%, and 7wt% change with time. Fig.15 As shown by Fig.15 It can be seen that the QC-OD hydrogel swelled rapidly on the first day and reached equilibrium at 4 to 6 days. At 9 days, the QC-OD hydrogel with a concentration of 3wt% was almost completely degraded, and the hydrogels with concentrations of 5wt% and 7wt% were mostly degraded.

[0128] Self-healing and adhesion properties of QC-OD hydrogels

[0129] Detection method: A piece of 5wt% QC-OD hydrogel was cut and adhered together. After 5 minutes, it was lifted up and the healing was observed. The self-healing and adhesion of the 5wt% QC-OD hydrogel were obtained as shown in the figure. Fig.16 As shown by Fig.16 It can be seen that QC-OD hydrogel has self-healing and adhesion properties.

[0130] Injectability of QC-OD hydrogel

[0131] Test method: put 5wt% QC-OD hydrogel into a 1mL syringe and push it out, write HUST in English, and get the injectability of 5wt% QC-OD hydrogel as shown in the figure below. Fig.17 As shown by Fig.17 It can be seen that QC-OD hydrogel is injectable.

[0132] Hemostatic ability of QC-OD@Au-FePS3 hydrogel prepared in Example 1

[0133] Detection method: SD rats were anesthetized with 10mL / kg 4wt% chloral hydrate and fixed on a surgical pad. The mouse liver was exposed through an abdominal incision, and a pre-weighed filter paper was placed on a paraffin film under the liver. A bleeding point was formed on the liver with the needle of a 1mL syringe, and then a hemostatic sponge, a QC-OD hydrogel with a concentration of 5wt%, or the QC-OD@Au-FePS3 hydrogel prepared in Example 1 was immediately placed on the bleeding point. A blank control group without any treatment was set up. After 3 minutes, the weight of the filter paper after absorbing blood was measured, and the actual picture of the mouse liver after treatment with the blank control group, the hemostatic sponge, the QC-OD hydrogel with a concentration of 5wt%, and the QC-OD@Au-FePS3 hydrogel prepared in Example 1 was as shown in the figure. Fig.18 As shown. Fig.18 It can be seen that the QC-OD@Au-FePS3 hydrogel prepared in Example 1 has good hemostatic ability.

[0134] Animal experiment: Healing of infected wounds in diabetic rats under different treatments.

[0135] Detection method: Sprague-Dawley rats (6 weeks) were obtained from Wuhan Shubaili Biotechnology Co., Ltd., China, and their use was approved by the Animal Research Ethics Committee of Tongji Medical College, Huazhong University of Science and Technology. Induction of diabetes: The rats were first fed a high-fat diet for four weeks, and then intraperitoneally injected with streptozotocin (50 mg / kg, Sigma, USA) for three days a day. Diabetes can be confirmed if the fasting blood glucose level is continuously higher than 11.1 mmol / L for three consecutive tests. Skin wound modeling and healing: Under sodium pentobarbital anesthesia (50 mg / kg), a full-thickness wound (15 mm in diameter) was made on the back of the rat with a sharp round punch. The wound was inoculated with 100 μL of Staphylococcus aureus suspension (3×10 8CFU / mL) for 10 minutes. Finally, PBS, 5wt% QC-OD hydrogel, QC-OD@Au-FePS3 hydrogel prepared in Example 1, and NIR and QC-OD@Au-FePS3 hydrogel prepared in Example 1 were used to treat the infected wounds of the above diabetic rats, and the actual pictures of the changes of the infected wounds of diabetic rats after different treatments over time were obtained. Fig.19 As shown. Fig.19 It can be seen that the QC-OD@Au-FePS3 hydrogel prepared in Example 1 can promote the healing of infected wounds in diabetic rats, and there is a synergistic effect between QC-OD hydrogel, Au-FePS3 nanosheets and NIR treatment.

[0136] In addition, the treatment of the single-atom nanozyme based on the red blood cell template disclosed in the prior art Chinese patent CN117772250A requires additional hydrogen peroxide to produce ROS to exert antibacterial and therapeutic effects. The Au-FePS3 nanosheets prepared by the present invention have GOx-POD cascade catalytic activity, which can directly decompose the glucose in the local diabetic wound surface to produce hydrogen peroxide, and further produce ROS to exert antibacterial ability.

[0137] Detection of antibacterial effects of different treatments on infected wounds in diabetic rats

[0138] Detection method: On the third day of the above animal experiment, wound tissue was collected and soaked in 1 mL PBS, and then 100 μL of the suspension was smeared on an agar plate and cultured at 37°C for 24 hours to obtain the antibacterial effect of different treatments on the infected wound surface of diabetic rats. Fig. 20 As shown. Fig. 20 It can be seen that the QC-OD@Au-FePS3 hydrogel prepared in Example 1 has excellent antibacterial ability, and the antibacterial ability of quaternary ammonium groups (QC-OD hydrogel), ROS (GOx-POD cascade activity) and photothermal effect (NIR treatment) has a synergistic effect.

[0139] Example 2

[0140] A method for preparing an antibacterial hydrogel loaded with gold-iron trisulfide phosphorus nanosheets comprises the following steps:

[0141] (1) 100 mg of FePS3 crystals were dispersed in 25 mL of N-methylpyrrolidone (NMP, AR, >99.0%), and then subjected to the first ultrasonic treatment in an ice bath at 800 W for 12 h, with an ultrasonic working time of 5 seconds and an interval of 3 seconds. The solution obtained by the first ultrasonic treatment was centrifuged at 4000 rpm for 10 min to remove large pieces, and then the supernatant was centrifuged at 14000 rpm for 30 min. The obtained precipitate was washed with ethanol and centrifuged at 14000 rpm for 30 min, and the precipitate was collected. After washing with water, the precipitate was centrifuged at 14000 rpm for 30 min, and the precipitate was collected. After freezing the precipitate at -20 ° C for 24 h, it was dried in a freeze dryer at a pressure of 2.0 Pa and a temperature of -80 ° C for 72 h to obtain 30 mg of FePS3 nanosheets;

[0142] Disperse 10 mg of FePS3 nanosheets in 40 mL of water to obtain an aqueous dispersion of FePS3 nanosheets;

[0143] (2) adding 2.4 g of polyvinyl pyrrolidone to the aqueous dispersion of FePS3 nanosheets obtained in step (1), ultrasonically dispersing for 30 min, then adding 2.5 mL of HAuCl4·3H2O (20 mM) and 2.5 mL of NaBH4 (20 mM), performing a second ultrasonic treatment at 300 W for 30 min, centrifuging the solution obtained by the second ultrasonic treatment at 14000 rpm for 30 min, washing the obtained precipitate with water and centrifuging at 14000 rpm for 30 min, collecting the precipitate, and drying the precipitate in an oven at 37° C. to obtain 13 mg of Au-FePS3 nanosheets;

[0144] (3) Weigh 5 g of dextran and dissolve it in 50 mL of deionized water to obtain a dextran solution; prepare a 100 g / L sodium periodate aqueous solution according to a molar ratio of dextran monomer to sodium periodate of 1:1.5; add the sodium periodate solution to the dextran solution, perform gelation reaction at room temperature and in the dark for 8 h, and then add 2 mL of ethylene glycol to terminate the reaction; dialyze using a dialysis bag with a molecular weight cutoff (MwCO) of 3500, and replace the dialysis solution every day. On the third day, the dialysis solution is clear and colorless. After placing the dialysis solution in a -80°C refrigerator for 1 day, place it in a freeze dryer for freeze drying to obtain a white product, oxidized dextran;

[0145] (4) preparing the Au-FePS3 nanosheets obtained in step (2) into an aqueous solution of Au-FePS3 nanosheets with a concentration of 1 mg / mL;

[0146] The oxidized dextran obtained in step (3) is prepared into an oxidized dextran aqueous solution having an oxidized dextran concentration of 7 wt %;

[0147] 200uL of the aqueous solution of the Au-FePS3 nanosheets, 357uL of the aqueous solution of the oxidized dextran, 357uL of the aqueous solution of quaternary ammonium chitosan with a concentration of 7wt% and 86ul of deionized water were mixed, stirred at 120rpm for 1min, and then allowed to stand at 25°C for 5min to obtain 1mL of the antibacterial hydrogel loaded with gold-iron trisulfide phosphorus nanosheets (abbreviated as QC-OD@Au-FePS3 hydrogel);

[0148] The concentration of QC-OD hydrogel in the antibacterial hydrogel loaded with gold-phosphorus iron trisulfide nanosheets is 5wt%.

[0149] Example 3

[0150] A method for preparing an antibacterial hydrogel loaded with gold-iron trisulfide phosphorus nanosheets comprises the following steps:

[0151] (1) 50 mg of FePS3 crystals were dispersed in 20 mL of N-methylpyrrolidone (NMP, AR, >99.0%), and then subjected to the first ultrasonic treatment in an ice bath at 600 W for 15 h, with an ultrasonic working time of 5 seconds and an interval of 3 seconds. The solution obtained by the first ultrasonic treatment was centrifuged at 4000 rpm for 10 min to remove large pieces, and then the supernatant was centrifuged at 14000 rpm for 30 min. The obtained precipitate was washed with ethanol and centrifuged at 14000 rpm for 30 min. The precipitate was collected, washed with water and centrifuged at 14000 rpm for 30 min. The precipitate was collected and dried in an oven at 37°C to obtain 14 mg of FePS3 nanosheets;

[0152] 14 mg of FePS3 nanosheets were dispersed in 40 mL of water to obtain an aqueous dispersion of FePS3 nanosheets;

[0153] (2) adding 2.4 g of polyvinyl pyrrolidone to the aqueous dispersion of FePS3 nanosheets obtained in step (1), ultrasonically dispersing for 30 min, then adding 3 mL of HAuCl4·3H2O (20 mM) and 3 mL of NaBH4 (20 mM), performing a second ultrasonic treatment at 400 W for 30 min, centrifuging the solution obtained by the second ultrasonic treatment at 14000 rpm for 30 min, washing the obtained precipitate with water and centrifuging at 14000 rpm for 30 min, collecting the precipitate, and drying the precipitate in an oven at 37° C. to obtain 15 mg of Au-FePS3 nanosheets;

[0154] (3) Weigh 5 g of dextran and dissolve it in 50 mL of deionized water to obtain a dextran solution; prepare a 100 g / L sodium periodate aqueous solution according to a molar ratio of dextran monomer to sodium periodate of 1:1.2; add the sodium periodate solution to the dextran solution, perform gelation reaction at room temperature and in the dark for 6 h, and then add 2 mL of ethylene glycol to terminate the reaction; dialyze using a dialysis bag with a molecular weight cutoff (MwCO) of 3500, and replace the dialysis solution every day. On the third day, the dialysis solution is clear and colorless. After placing the dialysis solution in a -80°C refrigerator for 1 day, place it in a freeze dryer for freeze drying to obtain a white product, oxidized dextran;

[0155] (4) preparing the Au-FePS3 nanosheets obtained in step (2) into an aqueous solution of Au-FePS3 nanosheets with a concentration of 1 mg / mL;

[0156] The oxidized dextran obtained in step (3) is prepared into an oxidized dextran aqueous solution having an oxidized dextran concentration of 7 wt %;

[0157] 200uL of the aqueous solution of the Au-FePS3 nanosheets, 357uL of the aqueous solution of the oxidized dextran, 357uL of the aqueous solution of quaternary ammonium chitosan with a concentration of 7wt% and 86ul of deionized water were mixed, stirred at 60rpm for 0.5min, and then allowed to stand at 37°C for 5min to obtain 1mL of the antibacterial hydrogel loaded with gold-iron trisulfide phosphorus nanosheets (abbreviated as QC-OD@Au-FePS3 hydrogel);

[0158] The concentration of QC-OD hydrogel in the antibacterial hydrogel loaded with gold-phosphorus iron trisulfide nanosheets is 5wt%.

[0159] In summary, the antibacterial hydrogel loaded with gold-iron trisulfide phosphorus nanosheets prepared by the present invention is of great significance for improving the high sugar, persistent infection and hypoxic microenvironment of diabetic wounds and promoting wound healing, and provides an effective strategy for the treatment of diabetic wounds.

[0160] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing an antibacterial hydrogel loaded with gold-iron trisulfide phosphorus nanosheets, characterized in that: The following steps are involved: (1) dispersing FePS3 crystals in N-methylpyrrolidone, and sequentially performing a first ultrasonic treatment and a first post-treatment to obtain FePS3 nanosheets; The FePS3 nanosheets are formulated into a water dispersion of FePS3 nanosheets; (2) mixing the aqueous dispersion of FePS3 nanosheets obtained in step (1) with polyvinyl pyrrolidone, adding HAuCl4·3H2O and NaBH4, and sequentially performing a second ultrasonic treatment and a second post-treatment to obtain Au-FePS3 nanosheets; (3) adding sodium periodate solution to the dextran solution, performing redox reaction at room temperature in the dark, and then performing dialysis, low temperature standing and freeze drying in sequence to obtain oxidized dextran; (4) preparing an aqueous solution of Au-FePS3 nanosheets obtained in step (2); preparing an aqueous solution of oxidized dextran obtained in step (3); The aqueous solution of the Au-FePS3 nanosheets, the aqueous solution of the oxidized dextran, the aqueous solution of quaternary ammonium chitosan and water are mixed, stirred and allowed to stand in sequence to obtain an antibacterial hydrogel loaded with gold-iron trisulfide phosphorus nanosheets.

2. The preparation method according to claim 1, characterized in that: The concentration of the aqueous dispersion of FePS3 nanosheets in step (1) is 0.1-0.5 mg / mL.

3. The preparation method according to claim 1, characterized in that: In the step (2), the ratio of the volume of the aqueous dispersion of FePS3 nanosheets to the mass of polyvinyl pyrrolidone is 10 mL: (0.3-1) g.

4. The preparation method according to claim 1, characterized in that: The ratio of the mass of FePS3 nanosheets in the aqueous dispersion of FePS3 nanosheets to the mass of HAuCl4·3H2O and NaBH4 in step (2) is 1 mg: (2×10 -3 ~8×10 -3 )mmol:(2×10 -3 ~8×10 -3 )mmol.

5. The preparation method according to claim 1, characterized in that: In the step (2), the molar ratio of the glucan monomer in the glucan solution to the sodium periodate in the sodium periodate solution is 1:(1-2).

6. The preparation method according to claim 1, characterized in that: In the step (4), the concentration of Au-FePS3 nanosheets in the aqueous solution of Au-FePS3 nanosheets is 0.5-2 mg / mL; the concentration of quaternary ammonium salt chitosan in the aqueous solution of quaternary ammonium salt chitosan is 5-10 wt%.

7. The preparation method according to claim 1, characterized in that: The standing temperature in step (4) is 25 to 37° C., and the standing time is 2 to 10 minutes.

8. The preparation method according to claim 1, characterized in that: In the step (4), the concentration of the quaternary ammonium salt chitosan-oxidized dextran hydrogel in the antibacterial hydrogel loaded with gold-phosphorus iron trisulfide nanosheets is 3-7 wt %.

9. An antibacterial hydrogel loaded with gold-phosphorus iron trisulfide nanosheets prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the antibacterial hydrogel loaded with gold-iron trisulfide phosphorus nanosheets as claimed in claim 9 in the preparation of a drug for treating diabetic wounds.

Citation Information

Patent Citations

  • Chemical preparation method for gold nanoparticle hydrosols

    CN102107283A

  • Antibacterial medical hydrogel dressing and preparation method thereof

    CN112472867A

  • Injectable hydrogel and preparation method thereof

    CN113769157A

  • Photo-thermal chemical power nano-composite as well as preparation method and application thereof

    CN115006525A

  • Thermo-sensitive black phosphorus hydrogel for promoting wound healing and preparation method of thermo-sensitive black phosphorus hydrogel

    CN115887647A

Cited By

  • Preparation method of iron-based nano cascade catalyst and application of iron-based nano cascade catalyst in sterilization and treatment of diabetic wounds

    CN120715213A